Education in Teschen Silesia from 1848 to 1914 - Zormanova , Lucie (Biuletyn Historii Wychowania, 2023)
The article focuses on the development of national education, Polish and Czech, in the territory of Teschen Silesia in 1848–1914 The first part of the article deals with the demographic changes that occurred at this time in the region, along with the development of industry. Moreover, the national issue and the national consciousness of the population are presented. In its second part, the article deals with the development of Polish and Czech education in the area, from preparatory high schools to secondary schools.